InGaAsP/InP Microring Resonator (MRR) Waveguide Used to Generate Soliton Comb with Tunable Channel Spacing - Alizadeh, F.; Hashim, M.N.; Ahmad, Harith; Amiri, I.S. (American Scientific Publishers, 2016)
A novel system of tunable channel spacing soliton comb generation is presented using a PANDA ring resonator incorporated with an add-drop filter system. The intense optical fields known as soliton comb can be generated. Results show that soliton comb can be generated with un-equal spaced or variable free spectral range (FSR) by using the input bright soliton pulse into the microring resonator (MRR) system. The proposed comb filter exhibits a large tuning range in channel spacing. Our simulations shows that the channel spacing can be continuously tuned form up to 10 GHz, where the centre wavelength of the input power has been selected at 50 GHz. The structure of the proposed MRR's waveguide (InGaAsP/InP) and mode propagation profile have been presented in this research.